Photocatalytic Materials and Photocatalytic Reactions - Sugang Meng (Molecules)
This Special Issue, titled “Photocatalytic Materials and Photocatalytic Reactions”, focuses on designing advanced photocatalysts, understanding their structure-dependent properties, and seeking to exploit them in the fields of energy conversion, pollutant degradation, artificial photosynthesis, organic synthesis, etc [...]